Materials on the frontier: A review on groundbreaking solutions for hydrogen storage applications - Siti Nurqurratulainie, Miskan; Bashir, Abubakar Abdulkadir; Herma Dina, Setiabudi (Elsevier B.V., 2025)
As global energy shifts toward sustainable solutions, switching to sustainable energy, particularly those involving energy storage from hydrogen, relies on effective storage technologies. This is necessary for harnessing the potential of hydrogen as a clean energy carrier. This review discussed the latest advancements in materials designed to improve hydrogen storage efficiency, safety, and scalability. The articles reported different storage materials, such as metal hydrides, chemical hydrides, advanced adsorbents, and their challenges and prospects. Developing innovations like nanostructured and hybrid materials are explained, showing how these cutting-edge approaches improve hydrogen kinetics. However, despite the advancements, challenges like feasibility and sustainability remain. Hence, this study discusses these barriers through life cycle assessments and recycling. Moreover, the study offers an understanding of the applications of these materials, illustrating their prospects to simplify a hydrogen economy. Through examining current research and identifying important trends, the article aims to illuminate the way forward for materials science in hydrogen storage applications. The findings highlight the importance of material development and emphasise the collaborative efforts researchers require to realise the potential of hydrogen as a keystone of sustainable energy systems.